2021
DOI: 10.3390/diagnostics11101782
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Accuracy in the Diagnosis of Anterior Talo-Fibular Ligament Acute Injury: A Systematic Review and Meta-Analysis

Abstract: Background: The studies about injury to the anterior talo-fibular ligament (ATFL) are focused mainly on chronic symptoms and chronic instability, and the literature about the accuracy of magnetic resonance imaging (MRI) in acute injuries is quite lacking. Methods: This systematic review with meta-analysis analyzes the diagnostic accuracy of MRI on acute ATFL injury. Relative studies were retrieved after searching three databases (MEDLINE, SCOPUS, and Cochrane Central Register of Controlled Trails). Eligible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Injuries of the ATFL are mostly located on its fibular side, while talar side injuries are uncommon [4,12,14,30], with a low incidence of 6-9% on MRI and ultrasound in ankle sprain patients [6,7,18]. In the present study, 50 of 1353 patients (3.7%) with CAI were confirmed intraoperatively with an injury at the talar side of ATFL (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Injuries of the ATFL are mostly located on its fibular side, while talar side injuries are uncommon [4,12,14,30], with a low incidence of 6-9% on MRI and ultrasound in ankle sprain patients [6,7,18]. In the present study, 50 of 1353 patients (3.7%) with CAI were confirmed intraoperatively with an injury at the talar side of ATFL (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Calceneofibular ligaments injury might be happened in main inversion strain, although it related with an anterior talofibular ligaments injury. On other hand, posterior talofibular ligaments are infrequently tom apart from case of entirely ankle dislocation [20]. Study by Helms et al, showed the ATFL is frequently torn ligaments in ankle joint.…”
Section: рис 3 мртmentioning
confidence: 99%
“…Subsequently, the medical analysis strategy used in this study is elaborated. As the most recent studies analyzed between 100 and 600 patients, and most of them classified the ligament in a more simplified fashion as normal ligament or altered ligament [ 14 , 17 ], this study made the difference between a normal, abnormal, and absent ligament, and so a larger sample was chosen.…”
Section: Experimental Setup and Performance Metricsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) provides optimal visualization of morphological changes in ankle ligament structures [ 5 , 6 , 7 , 8 ], however, the present set of literature lacks an accurate definition of a normal ATFL morphology [ 9 , 10 , 11 , 12 ]. Moreover, low accuracy is also observed in many studies [ 12 , 13 , 14 ] which could be due to the fact that it is a static exam used to study a structure that performs dynamic joint control. Further, it can potentially produce false negatives for ligament lesions, which would occur if the ligament was subjected to a yo-yo effect [ 11 , 13 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%